2016
DOI: 10.1097/cej.0000000000000132
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis on vitamin D receptor and cancer risk

Abstract: Vitamin D plays a significant role in our health, including cancer incidence and mortality. Vitamin D receptor (VDR) single-nucleotide polymorphisms (SNPs) may affect its activity, influencing the risk of cancer. Several studies have investigated VDR SNPs, but the association with the risk of cancer is controversial. Here, we present a meta-analysis to assess the association of TaqI, ApaI, and Cdx2 SNPs with the risk of cancer. A systematic literature search was performed following a predefined protocol and us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 110 publications
(65 reference statements)
0
13
1
Order By: Relevance
“…Gandini and colleagues reviewed 79 studies involving more than 52,000 different cancer cases and 62,000 controls to identify relevance of VDR BsmI, FokI, ApaI and TaqI polymorphism for various cancers and found BsmI, FokI and TaqI to be associated with CRC [ 27 ]. While we observed the ‘C’ allele of VDR-ApaI to confer 77% increased risk for CRC in patients > 57 years of age at the time of disease diagnosis, a recent meta-analysis by Serrano et al did not identify higher risk of CRC with VDR-ApaI but found a significant association with VDR-TaqI polymorphism [ 44 ]. Several other studies did not find an association of these VDR genetic variants with colorectal cancer risk in Caucasian populations [ 28 – 30 ].…”
Section: Discussioncontrasting
confidence: 61%
“…Gandini and colleagues reviewed 79 studies involving more than 52,000 different cancer cases and 62,000 controls to identify relevance of VDR BsmI, FokI, ApaI and TaqI polymorphism for various cancers and found BsmI, FokI and TaqI to be associated with CRC [ 27 ]. While we observed the ‘C’ allele of VDR-ApaI to confer 77% increased risk for CRC in patients > 57 years of age at the time of disease diagnosis, a recent meta-analysis by Serrano et al did not identify higher risk of CRC with VDR-ApaI but found a significant association with VDR-TaqI polymorphism [ 44 ]. Several other studies did not find an association of these VDR genetic variants with colorectal cancer risk in Caucasian populations [ 28 – 30 ].…”
Section: Discussioncontrasting
confidence: 61%
“…However, many of these studies presented significant associations [ 35 , 38 ]. Indeed, in a meta-analysis conducted by Serrano et al, [ 39 ] the authors presented a significant increased risk for CRC in the presence of tt and aa genotypes, with strong frequency variations present among different ethnic groups. Moreover, Gandini et al, [ 24 ] reviewed 79 studies with more than 52,000 cancer cases, including CRC patients, and 62,000 controls, and demonstrated that Bsm I, Fok I and Taq I polymorphisms are associated with CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is well known to be implicated in the development and recurrence of breast cancer [10]; here we hypothesize that vitamin D action in adipose tissue may partially explain the role of vitamin D in cancers. The most common VDR polymorphisms reported to be associated with cancer and obesity are BsmI (rs1544410), ApaI (rs7975232), TaqI (rs731236), FokI (rs2228570) and Cdx2 (rs 11,568,820) [11, 12]. Likewise, previous epidemiologic studies indicate that obesity is associated with low levels of 25-hydroxy vitamin D3(25(OH) [13].…”
Section: Introductionmentioning
confidence: 99%